2020
DOI: 10.1073/pnas.2009502117
|View full text |Cite
|
Sign up to set email alerts
|

Towards the molecular architecture of the peroxisomal receptor docking complex

Abstract: Import of yeast peroxisomal matrix proteins is initiated by cytosolic receptors, which specifically recognize and bind the respective cargo proteins. At the peroxisomal membrane, the cargo-loaded receptor interacts with the docking protein Pex14p that is tightly associated with Pex17p. Previous data suggest that this interaction triggers the formation of an import pore for further translocation of the cargo. The mechanistic principles, however, are unclear, mainly because structures of higher-order assemblies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…PEX17 is characterized by a single transmembrane helix at the N-terminal. As described above, S. cerevisiae PEX14 and PEX17 together form a rod-like structure at the peroxisomal membrane ( Lill et al, 2020 ). PEX33 is a paralog of PEX14, whereas PEX17 is a protein partially aligning to the C-terminal of PEX14 and PEX33, suggesting PEX17 is a PEX14-like protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PEX17 is characterized by a single transmembrane helix at the N-terminal. As described above, S. cerevisiae PEX14 and PEX17 together form a rod-like structure at the peroxisomal membrane ( Lill et al, 2020 ). PEX33 is a paralog of PEX14, whereas PEX17 is a protein partially aligning to the C-terminal of PEX14 and PEX33, suggesting PEX17 is a PEX14-like protein.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, only in Opisthokonta organisms (Fungi and Metazoa) and amoebozoa, PEX13 has a predicted SH3 domain at the C-terminal ( Supplementary Figure 1A ), which likely controls its interaction with other proteins. PEX14 also contains a predicted transmembrane helix, but seems to be largely structurally disordered ( Supplementary Figure 1B ), although it also includes several coiled-coil domains (e.g., Lill et al, 2020 ). In vitro protease protection experiments using human PEX13 and PEX14 confirmed that both proteins are integral membrane proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first talk was given by Pascal Lill (Christos Gatsogiannis Laboratory, Max Planck Institute of Molecular Physiology, Dortmund, Germany), who presented a structural characterization of the main components of the peroxisomal docking complex in S. cerevisiae, Pex14 and Pex17. Pascal and his colleagues applied cryo-electron microscopy single particle analysis and cryo-electron tomography on purified complexes and found that three copies of Pex14p and a single copy of Pex17p assemble to form a 20 nm rod-like particle (Lill et al 2020). The different subunits are arranged in a parallel manner, showing interactions along their complete sequences and providing receptor-binding sites on both membrane sides.…”
Section: Session 1: Chair: Noa Dahan Weizmann Institute Of Science Israelmentioning
confidence: 99%